Communities of practice, social learn-ing and networks: Exploiting the social side of coach development - Stoszkowski, J.; Collins, D. (Sport, Education and Society, 2014)
Large-scale coach education programmes have been developed in many countries, and are presented as playing a key role in the development of coaches and the promotion of high standards. Unfortunately, however, coaches often perceive that the current system of formal coach education fails to meet their needs. Perhaps as a result, the majority of their development is personally perceived to take place via informal and non-formal means. Appropriately, therefore, there has been an increasing focus within the coaching literature on the social aspects of learning, with social constructivist perspectives receiving particular attention. Reflecting this appropriate focus, this article explores some of the potential opportunities and threats that social learning methods, such as Communities of Practice (CoP), present for coach developers. In tandem, we outline how all coaches are influenced by a set of pre-existing beliefs, attitudes and dispositions, which are largely tempered by their experiences and interactions both with and within their social `milieu`. We argue that, at the very least, we need to begin to understand these constructs and, if we do, the potential for coach developers to manipulate and exploit them is obvious. In conclusion, it is highlighted that whilst offering inherent challenges, CoPs and other social learning methods provide coach developers with a great opportunity and legitimate tool to change coach behaviour and raise coaching standards. Perhaps paradoxically, we also propose that formal coach education may still have a vital role to play in this process.